Complex Modernization of Public Infrastructure and Hospitality as a Factor in the Sustainable Development of the City in Ukraine - Melnykova, Maryna; Gradoboіeva, Yеlyzaveta; Mirzodaeva, Tetiana; Ragulina, Nadiia (My University, 2020)
The sustainable development of the city involves the solving of economic, environmental and social problems through the modernization of various spheres of the urban economy. The modernization of related and interrelated spheres of the city’s economy should be based on an integrated approach. The hospitality and public infrastructure are such spheres. Their relationship is due to both technical and technological features and the possibilities of achieving the goals of sustainable development of the city (the hospitality sector contributes to the growth of openness of the city and the life support and environmental sustainability of the city directly depends on the state and development of public infrastructure). The priorities of the modernization of public infrastructure and hospitality for sustainable development of the city have been determined. The condition of the public infrastructure and hospitality in cities of Ukraine was analyzed from the point of view of modernization for sustainable development. The experience of modernization of public infrastructure and hospitality in sustainable European cities (including improving energy efficiency, strengthening environmental safety, creating a barrier-free environment) has been studied. The technical, technological, financial and institutional features that determine the feasibility of modernizing the public infrastructure and hospitality based on the principles of an integrated approach have been determined. The recommendations of the mechanism of public-private partnership using in the implementation of projects for the modernization of public utilities infrastructure and hospitality of the city have been developed. The decision-making tools for managing resources have been proposed for the justification and implementation of a project to modernize public infrastructure and hospitality based on a comprehensive approach.
Keywords: city; public infrastructure; sustainable development; hospitality; integrated approach; modernization; гостинність; інфраструктура; кафедра туристичного та готельного бізнесу; сталий розвиток